If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -14 = -3x + 6 Reorder the terms: -14 + 7x = -3x + 6 Reorder the terms: -14 + 7x = 6 + -3x Solving -14 + 7x = 6 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -14 + 7x + 3x = 6 + -3x + 3x Combine like terms: 7x + 3x = 10x -14 + 10x = 6 + -3x + 3x Combine like terms: -3x + 3x = 0 -14 + 10x = 6 + 0 -14 + 10x = 6 Add '14' to each side of the equation. -14 + 14 + 10x = 6 + 14 Combine like terms: -14 + 14 = 0 0 + 10x = 6 + 14 10x = 6 + 14 Combine like terms: 6 + 14 = 20 10x = 20 Divide each side by '10'. x = 2 Simplifying x = 2
| 3(x-1)(x+1)=9 | | 7+(1)(-2)= | | 7(1)+(-2)= | | 7(1+-2)= | | 3(2x-1)=4(x+2) | | 7(7x-2)=49x-14 | | -5+2(4)= | | -5(2)+4= | | y-4=-2/3x | | -5(1-2n)=15 | | -5(2+4)= | | 9x+7=-5+7x+16 | | -3(t+3)=15 | | 47-15=4(x-6) | | 70+5y-32=17y-11-5y | | 2+(-3)(4)= | | (36m-9mn=45n)/9 | | k^2+2k+-60=0 | | -4(p+5)= | | 4(2x+9)=-7x-24 | | 2(-3+4)= | | 50+3x= | | 5=-5a+2a | | 4(k+0.5)=2k+k+6 | | 1000x+2500=-4000 | | 4*x^2*(x^2-1)=17*x^2-25 | | 17-3(2x-7)=7x-3(2x-1)equation | | 4*x^2*(x-1)=17*x^2-25 | | 16=-11a+2a | | 2(x-1)(x+1)=8 | | x^2*(x^2-1)=17*x^2-25 | | x^2*(x-1)=17*x^2-25 |